Effect of water quality and substrates in the production of stevia seedlings (Stevia rebaudiana Bertoni) - Moguel Ordóñez, Yolanda; Ramírez Jaramillo, Genovevo; Tepal Chalé, Justo (Revista Mexicana de Ciencias Agrícolas, 2018)
The production of seedlings by cuttings for the sowing of stevia, is one of the most used methods in Mexico and in the world, for the economic and its relative ease to make them; however, the production of Stevia rebaudiana Bertoni seedlings with cuttings is limited by the use of very hard waters with high electrical conductivity, so that sometimes the roots do not develop and the cuttings dry up. The objective of the work was to evaluate three types of substrates and three water qualities, in the development of S. rebaudiana seedlings in the state of Yucatan. The study was carried out in Muna Yucatan, and three types of substrates were tested (commercial foam, moss-based mixture and coconut fiber) and three qualities of irrigation water (2 130 ppm, 1 230 ppm and 330 ppm of dissolved solids total) in the production of seedlings of the Morita II variety. The 100 cuttings were established per treatment and the length (cm) of the root and the height of the seedling were measured every 10 days. An effect of the type of substrate (p< 0.05) on seedling height and root size was found. With regard to water quality, an effect was found on the seedling height (p< 0.05), but not on the length of the root (p> 0.05). It is concluded that the substrate based on mixture of moss and coconut fiber formed roots in less time and produced higher seedlings. This is an advantage since the production time is reduced and there is a greater probability of survival of seedlings to the transplant.